IMPLEMENTATION OF PLACING TRANSMIGRATION CITIZENS IN CREATING AN INDEPENDENT COMMUNITY IN AYUMOLINGO VILLAGE, PULUBALA DISTRICT, GORONTALO REGENCY - sudarsono; Yosef p. Koton; abdurahman (Journal of Economic, Business, and Administration (JEBA), 2023)
ABSTRACTThis study aims to determine the implementation of the placement oftransmigration residents in realizing an independent society in AyumolingoVillage, Pulubala District, Gorontalo Regency and the factors that hinder theimplementation of Transmigration Residents' placement in creating anIndependent Society in Ayumolingo Village, Pulubala District, andGorontalo Regency.Research method used is a qualitative research method with data collectiontechniques including: 1) observation; 2) interview; and 3) documentation.Activities in data analysis, namely: 1) data reduction stage; 2) datapresentation stage; and 3) data verification stage.The results in this study are the implementation of the placement oftransmigration residents from planning has not been maximized because itdoes not include or involve residents around the transmigration area or areaas required and the implementation is not optimal because it still causes socialjealousy of local residents and complaints from transmigration residentsbecause the land is determined/given by the government is not in accordancewith what is in the location of the transmigration area and the supervisionhas not been effective, so that there are transmigration residents whohave been placed away from their homes/settlement locations, so that thegovernment's goal in an effort to achieve business independence and maketransmigration residents feel at home or settle in the location of the transmigrationarea has not can be realized. As for the factors that hinder the implementationof the placement of Transmigration Citizens in AyumolingoVillage, Pulubala District, Gorontalo Regency, namely commitment is stilllow, transparency is still lacking and human resources are still limited, bothimplementing apparatus resources and community resources, thus hamperingthe implementation and implementation placement of transmigrants.